The Economic Value of Time in Arab Culture: New Evidence using Zimbardo Time Perspective Inventory (ZTPI) - Aldulaimi, Saeed H.; Abdeldayem, Marwan M. (American Journal of Social Sciences and Humanities, 2018)
The purpose of this study is to investigate the “time perspective” (TP) in the Arab culture in particular, how Arab people look at their commitments in life in terms of time relation such as appointment, deadline and punctuality. We adopted Zimbardo Time Perspective Inventory (ZTPI) as a questionnaire survey that was directed to a sample of 122 individuals from 5 different Arab countries namely: Bahrain, Egypt, Iraq, Jordan and Sudan. These countries were chosen to ensure representation of high, middle and low income countries. The research instrument consists of 56 different items that measure the five time perspective dimensions: Past-Negative (PN), Past-Positive (PP), Present-Hedonistic (PH), Present-Fatalistic (PF) and Future (F) (Zimbardo and Boyd, 1999). The overall reliability of the questionnaire is 0.868 and the reliability levels for the five main dimensions of TP were found to be satisfactory as measured by Cronbach Alpha. The findings reveal that Arab people are respecting many social norms and the Present-Hedonistic (PH) with a mean of 48.6 scored the highest value among the five dimensions of TP followed by the Future (F) dimension with a mean value of 43.9. However, the Present Fatalistic (PF) with a mean of 30.0 scored the lowest value. Hence, we concluded that Arab people participated in this study are mainly oriented by the present-hedonistic and future and are not really oriented by fatalistic issues. In addition, the results indicate that there are significant differences among the five dimensions of TP and no balance in TP is recognized as a main prerequisite for psychological health, happiness, satisfaction in life, self-esteem and general wellbeing. The significance of this study lies in the fact that this is the first study of its kind that applied the ZTPI model in the Arab World. This study recommends that future research should address the use of a wider pool of participants and include some control variables such as age, education, and geographic location. Further attention should also be given to get insights from the psychology literature to determine the proper way of changing the time perspective.